The Effect of Strategic Orientation on Green Supply Chain Practices and Performance: A Case of Manufacturing Companies in Pakistan - Nadeem, Kawish; Siddiqui, Danish Ahmed (Asian Business Review, 2017)
The aim of this study is to find out the direct impact of competence of strategic supply chain orientation, strategic environmental orientation and institutional pressure on Green Supply Chain Management (GSCM) and to overall performance. The data gathered from executives of 66 manufacturing firms of Pakistan. On the one hand, the relationship between strategic orientations of the environment, supply chain, institutional pressure, and adoption of GSCM practices is examined on the other hand GSCM practices, and its relationship with performance measures including Customer Effectiveness, Environmental Differentiation, Economic Performance, Operational Efficiency and Social Performance is examined. The Smart PLS software is used to compute content validity, convergent validity, discriminant validity, and predictive relevance model. The companies in Pakistan are less oriented towards environment and supply chain. However, due to the pressure from institutes, they are persuaded to adopt GSCM practices in their operations, which eventually boost their performance. The outcome of GSCM practices results in saving the environment, creating a better social image, cost reduction and profitability which would enable managers to be able to know strategic orientations (both environmental and SCM) rather than depending on the issues of institutional pressures and monitoring directions of strategies for Green SCM.
Keywords: Green Supply Chain; strategic orientations; institutional pressure; operational efficiency; customer effectiveness; social and economic performance; environmental differentiation